Genetic diversity and haplotypes of Echinococcus granulosus isolated from cattle and buffaloes and first report of E. ortleppi (G5) in buffaloes in Pakistan based on mitochondrial cytochrome c oxidase subunit-1 gene (mt-CO1) markers - Khan, Huma; Celik, Figen; Simsek, Sami; Harandi, Majid Fasihi; Ahmed, Haroon (Academic Press Inc Elsevier Science, 2023)
Cystic echinococcosis (CE) is a parasitic disease that is caused by larval stage of Echinococcus granulosus tapeworm, one of the most important and neglected zoonotic disease. Although the echinococcosis is endemic in the neighboring countries, information regarding circulating genotypes of E. granulosus sensu lato is scarce in Pakistan. Therefore, the main purpose of this report was to contribute in molecular epidemiology and to find genetic variation and haplotypes of E. granulosus s.l. in cattle and buffalo isolates. To identify species circulating in country, parasite samples were collected from different slaughterhouses and butcher shops of two major cities, Rawalpindi and Peshawar located in Punjab and Khyber Pakhtunkhwa (KP) provinces, Pakistan, respectively. A total of 100 CE cyst samples were investigated from buffalo (n = 61), and cattle (n = 39) hosts. After genomic DNA extraction from individual cyst materials, mt-CO1 (875 bp) gene was amplified by PCR. After that, PCR products were electrophoresed on the agarose gel then purified and sequenced using forward primer. The sequences were trimmed (779 bp), aligned and matched with NCBI published sequences. E. granulosus s.s. (G1, G3) (71.4%; n = 20/28) was confirmed as the dominant species in buffalo and cattle. E. ortleppi (G5) (28.6%; n = 8/ 28) was recorded for the first time in both buffalo and cattle isolates from Rawalpindi. E. granulosus s.l. haplotype network showed single predominant haplotype, which comprised 40% of population. Tajima's D and Fu's Fs were negative and significant for E. ortleppi (G5), suggesting population expansion in Pakistan. Therefore, more studies using isolates of E. granulosus s.l. from various locations and intermediate hosts across Pakistan will add new data on molecular epidemiology and genotyping for effective control strategies of CE in Pakistan.
Keywords: Cystic echinococcosis; E. granulosus sensu stricto; E. ortleppi; Cattle; Buffalo; CO1; Haplotype; Pakistan